Recent insights into gap junction biogenesis in the cochlea. Issue 2 (26th September 2022) - Defourny, Jean; Thiry, Marc
Abstract: In the cochlea, connexin 26 (Cx26) and connexin 30 (Cx30) co‐assemble into two types of homomeric and heteromeric gap junctions between adjacent non‐sensory epithelial cells. These channels provide a mechanical coupling between connected cells, and their activity is critical to maintain cochlear homeostasis. Many of the mutations in GJB2 or GJB6, which encode Cx26 and Cx30 in humans, impair the formation of membrane channels and cause autosomal syndromic and non‐syndromic hearing loss. Thus, deciphering the connexin trafficking pathways in situ should represent a major step forward in understanding the pathogenic significance of many of these mutations. A growing body of evidence now suggests that Cx26/Cx30 heteromeric and Cx30 homomeric channels display distinct assembly mechanisms. Here, we review the most recent advances that have been made toward unraveling the biogenesis and stability of these gap junctions in the cochlea. Key Findings: Cx26/Cx30 heteromeric and Cx30 homomeric channels display distinct assembly mechanisms Cadherin‐based tricellular adherens junctions promote the microtubule‐mediated trafficking of Cx26/Cx30 oligomers to the cell surface and further assembly into GJPs Ephrin‐B2 promotes the assembly and sequestration of Cx30 GJPs into caveolae membrane domains in a cell‐autonomous manner